Pengukuran Kinerja Anggaran Atas Pengendalian Internal Dan Partisipasi Anggaran Survey Pada Lembaga Ilmu Pengetahuan Indonesia - Padriachyarsyah; Asyari; Dipa Teruna (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
Budgeting in government organizations is carried out through the concept of performance-based budgeting which is a reform in the field of planning and budgeting since 2005. The legal basis for planning and budgeting is regulated in Law Number 17 of 2003 concerning State Finance and Law Number 25 of 2004 concerning the National Financial System. National Development Planning. As a follow-up to this Law, the government issued Government Regulation Number 21 of 2004 concerning the Compilation of Work Plans and Budgets for State Ministries/Institutions. The research objective was to examine the effect of the internal control system on budget performance and the effect of budgetary participation on budget performance at the Indonesian Institute of Sciences. The research method used is quantitative descriptive with LIPI employee respondents as a population and the research sample is 90 LIPI Jakarta employees. Methods Data analysis was carried out with the classical assumption test and linear regression test and hypothesis test. With the help of SPSS 20, the research results were obtained. The results of the study show that internal control has a significant positive effect on budget performance and budget participation has a significant effect on budget performance